An Efficient Synthesis of Milnacipran Hydrochloride via Reductive Amination of Aldehyde - Neha Reddy Desireddy; Arava Glory; Krishna Reddy Bhimireddy; Yadagiri Kurra; Ram Reddy (Journal of Chemistry)
An efficient synthesis of milnacipran hydrochloride has been accomplished. The important application of this paper is the reductive amination of aldehyde to primary amine with water soluble reagents. This method provides a high yield of primary amine as the major product, reduces the number of steps, and discourages by-products.